Foudroyant Course of an Extensive Clostridium septicum Gas Gangrene in a Diabetic Patient with Occult Carcinoma of the Colon. (20th June 2013) - Hartel, Maximilian; Kutup, Asad; Gehl, Axel; Zustin, Jozef; Grossterlinden, Lars G.; Rueger, Johannes M.; Lehmann, Wolfgang
Abstract : Background . Spontaneous gas gangrene is a rare disease in which Clostridium septicum frequently can be detected. After an incubation period of 5–48 hours, a very painful swelling is accompanied by a rapidly spreading toxic-infectious clinical picture ultimately leading to septic shock and multiple organ failure. We present a case of a completely documented rare infectious disease with triage findings including initial vital signs, initial medical findings, and the emergency lab., radiological, intraoperative, histopathological, microbiological, and postmortem results. After initial diagnosis of the underlying disease, the patient has been immediately transferred to the operating theatre. The laboratory findings reflect the devastating effect of toxin α which is a toxin typically produced by C. septicum. The patient presented both an anaemia and a manifest coagulopathy as well as an onset of multiple organ failure. Despite the aggressive medical and surgical measures that have been taken, this patient could not be saved. Discussion . The case presented vividly emphasises the difficulty to identify these cases early enough to save a patient. This documentation may help health care providers to identify this life threatening disease as early as possible in future cases.